Comprehensive Guide to Autism - Patel, Vinood B.; Preedy, Victor R.; Martin, Colin R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Autism is a complex multifaceted disorder affecting neurodevelopment during the early years of life and which for many remains throughout adulthood. Inherent features include difficulties or deficits in communication, social interaction and cognition, person-to-person behavioral coordination and recall, to name but a few facets. It impacts on the affected individual, family and in some cases localized communities. The increased prevalence of childhood autism has resulted in rapid developments in a wide range of disciplines in recent years, though despite intensive research however, the identification of young children is difficult, the cause(s) remain unresolved and no single treatment strategy is employed. To address these issues, A Comprehensive Guide to Autism is an all embracing reference that offers analyses and discussions of contemporary issues in the field of autism. The objective of this book is to bring together scientific material from leading experts in the field relating to a wide range of important current topics. These include the early identification of autistic children and subsequent treatment, to social and behavioral studies. The editors also recognize that recent developments in genetic and immunological studies, the influence of diet, models of autism, and future treatment methods are essential reading for behavioral science researchers, psychologists, physicians, social workers, parents, and caregivers.
Section i: diagnosing autism spectrum disorders -- section ii: behavioral issues in autism spectrum disorders -- section iii: learning issues in autism spectrum disorders -- section iv: social issues in autism spectrum disorders -- section v: principal factors and contributing mechanisms in the pathophysiology of autism -- section vi: immunology of autism spectrum disorders -- section vii: genetics of autism spectrum disorders -- section viii: models of autism -- section ix asperges syndrome and adult autistics -- section x: treatments in autism.
Keywords: Philosophy (General).; Pediatrics; Social work; Psychology, clinical; Developmental psychology; Psychology; Neuropsychology; Pediatrics; Child and School Psychology; Social Work